Tanay gateway destination - Hernandez, Ida Talia A. (College of Architecture, University of the Philippines Diliman, 2018)
Tanay is an emerging tourist destination in Rizal Province. Dubbed as the Home of Adventure and Nature Experience, this town boasts a lot of natural wonders and exciting landscapes, along with various man-made historical, and religious structures, resorts and adventure camps. The town is also rich in history, arts, and culture; a home to vibrant festivals, arts such as rock balancing and painting, and a variety of local cuisine. The research focused on the Tanay Poblacion, which is an important entry point for its tourism and a venue for its arts and culture. Although the tourist destinations look promising, the town apparently needs to upgrade its tourist facilities and provide spaces for the promotion and development of its arts and culture. With the aim to address the following agenda -- tourism, transportation, and history, arts, and culture -- the project identified is a mixed-use tourism and cultural facility to be located along one of Tanay's major thoroughfares. The project, a gateway destination, will capture arriving travelers (particularly commuters) and provide a transfer point to the tourist destinations. Facilities that will showcase the town's cultural heritage are also included as an attraction for the tourists. The form, which takes inspiration from the Sierra Madre, seeks to image the town's landscape and become a landmark for Tanay's tourism and cultural heritage.